Effects of water depth on the growth of nelumbo nucifera gaertn. Seedlings - Alfasane, Md Almujaddade; Khondker, Moniruzzaman; Begum, ZN Tahmida (Dhaka University Journal of Biological Sciences, 2011)
Water depth showed significant effect on the growth of Nelumbo nucifera Gaertn. in deep and shallow water culture pits. In deep water culture pit, the leaf area showed its highest growth rate of 21.84 ± 2.89 cm2/day in summer and petiole length showed highest growth rate of 0.34 ± 0.10 cm/day in monsoon. The plantlets grown in shallow water culture pit showed highest growth rate of leaf area of 8.75 ± 0.91 cm2/day in summer and the length of the petiole was highest in monsoon (0.25 ± 0.03 cm/day). Comparatively highest growth was observed in deep water culture pit rather than that of shallow water. Highest growth of the plant and flowering were found to be associated with higher water depth (100 cm) where the plant grew up to a height of about 1.5 m and maximum leaf diameter was 50 cm. Poor growth of the plant with no flowering was in shallow water depth (20 cm) where maximum height of the plant was about 0.5 m and leaf diameter was 25 cm. Although the concentrations of NO3?N, soluble reactive phosphorus, soluble reactive silicate, planktonic chl a and phaeopigment were in higher amount in shallow water culture pit but due to shallow depthness plant showed poor growth and no flowering. Key words: Water depth; Limnological factors; Growth; Nelumbo nucifera DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8952 DUJBS 2010; 19(2): 111-118